Between byte and bark : Singapore, US & Chinese tech - Jayakumar, Shashi (2020)
Investment by China’s tech companies in Singapore has picked up considerable pace in recent months. Alibaba, ByteDance and Tencent have all made an intent to anchor a presence in Singapore that can tap on Southeast Asia’s burgeoning consumer markets. At what price?